1991
DOI: 10.1093/bja/67.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Effect of P6 Acupressure on Postoperative Vomiting in Children Undergoing Outpatient Strabismus Correction

Abstract: A prospective, double-blind study was conducted to compare the effect of pressure at the P6 (Neikuan) point with placebo as an antiemetic in children. Sixty-six patients, ages 3-12 yr, undergoing outpatient surgery for correction of strabismus, were allocated randomly to receive either bilateral P6 acupressure or placebo during the perioperative period. The study was designed to detect a 50% difference in the incidence of postoperative vomiting between the two groups, with a 90% power of achieving a statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
4

Year Published

1992
1992
2019
2019

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(49 citation statements)
references
References 0 publications
1
44
0
4
Order By: Relevance
“…12 However, a recent study of acupressure in paediatric strabismus repair found no antiemetic effect when compared with placebo. 22 Although the duration of postoperative recovery and the time to discharge from hospital were not different among the groups, this study confu'med our clinical suspicion that children who receive droperidol were more likely to be restless postoperatively. It should be noted that according to our definition of restlessness, 30% of children not receiving droperidol were also restless.…”
Section: Discussionmentioning
confidence: 56%
“…12 However, a recent study of acupressure in paediatric strabismus repair found no antiemetic effect when compared with placebo. 22 Although the duration of postoperative recovery and the time to discharge from hospital were not different among the groups, this study confu'med our clinical suspicion that children who receive droperidol were more likely to be restless postoperatively. It should be noted that according to our definition of restlessness, 30% of children not receiving droperidol were also restless.…”
Section: Discussionmentioning
confidence: 56%
“…Most trials recruited healthy adults undergoing elective surgery. Seven trials recruited children (Butkovic 2005;Lewis 1991;Rusy 2002;Schlager 1998;Shenkman 1999;Wang 2002;Yentis 1992). One trial recruited both children and adults (Amir 2007).…”
Section: Description Of Studiesmentioning
confidence: 99%
“…There were 10 types of P6 acupoint stimulation: needle acupuncture (Dundee 1986;Dundee 1989;Sharma 2007;Streitberger 2004;Yentis 1992); infiltration of dextrose (Tavlan 1996;Wang 2002;Yang 1993); semipermanent needles (Andrzejowski 1996); electrical stimulation of needles (Amir 2007;Dundee 1989;Ho 1989;Rusy 2002); transcutaneous electrical nerve stimulation (Fassoulaki 1993;Gan 2004;Habib 2006;Ho 1989); laser stimulation (Butkovic 2005;Schlager 1998); an acu-stimulation device (White 2002;Zarate 2001); and acupressure (Agarwal 2000;Agarwal 2002;Alkaissi 1999;Alkaissi 2002;Allen 1994;Barsoum 1990;Duggal 1998;Ferrara-Love 1996;Gieron 1993;Harmon 1999;Harmon 2000;Ho 1996;Klein 2004;Lewis 1991;Samad 2003;Schultz 2003;Turgut 2007). Two studies used conventional peripheral nerve stimulation (Arnberger 2007;Liu 2008).…”
Section: Description Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations